Analysis of Emotion Regulation in Spanish Adolescents: Validation of the Emotion Regulation Questionnaire - Gómez-Ortiz, Olga; Romera, Eva M.; Ortega-Ruiz, Rosario; Cabello, Rosario; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2016)
Emotion regulation (ER) is a basic psychological process that has been broadly linked to psychosocial adjustment. Due to its relationship with psychosocial adjustment, a significant number of instruments have been developed to assess emotion regulation in a reliable and valid manner. Among these, the Emotion Regulation Questionnaire (ERQ; Gross and John, 2003) is one of the most widely used, having shown good psychometric properties with adult samples from different cultures. Studies of validation in children and adolescents are, however, scarce and have only been developed for the Australian and Portuguese populations. The aim of this study was to validate the Spanish version of the ERQ for use in adolescents and determine possible differences according to the gender and age of young people. The sample consisted of 2060 adolescents (52.1% boys). Exploratory and Confirmatory factor analysis (EFA and CFA), multi-group analysis and Two-way multivariate analysis of variance (MANOVA) were performed and the percentiles calculated. The results of the AFE and CFA corroborated the existence of two factors related to the emotion regulation strategies of cognitive reappraisal and expressive suppression, showing acceptable internal consistency and test-retest reliability. Both factors also showed good criterion validity with personality traits, self-esteem, and social anxiety. Differences in cognitive reappraisal were found with regard to age, with younger students exhibiting the greatest mastery of this strategy. Gender differences were observed regarding the expressive suppression strategy, with boys being more likely to use this strategy than girls. A gender-age interaction effect was also observed, revealing that the use of the expressive suppression strategy did not vary by age in girls, and was more widely used by boys aged 12–14 years than those aged 15–16 years. However, we found evidence of measurement invariance across sex and age groups. The results suggest that the ERQ is a valid and reliable instrument that can be used to evaluate emotion regulation strategies in adolescents.